Self Expression Lyrics of Yura Yunita's Song Tenang: Van Dijk's Critical Discourse - Nella Viana Nur Ramadhanti; Abrian, Rizky (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to reveal that self-expression in the song lyrics can influence people's views on the issues they experience contained in the lyrics of Yura Yunita's song